L-Theanine Alleviates IMQ-Induced Psoriasis Like Skin Inflammation by Downregulating the Production of IL-23 and Chemokines - Xu, Yaohan; Zhu, Jiang; Hu, Jingyi; Zou, Ziqi; Zhao, Yueling; Lai, Lihua; Xu, Ping; Song, Yinjing; Cheng, Hao (Frontiers in Pharmacology, 2021)
Psoriasis, the most common skin inflammatory disease, is characterized by massive keratinocyte proliferation and immune cell infiltration into epidermis. L-Theanine (L-THE), a nonproteinogenic amino acid derived from green tea (Camellia sinensis), has been proved to possess the properties of anti-inflammatory, antidepressants and neuroprotective. However, whether L-THE has a therapeutic effect on psoriasis is still unknown. In this study, we found that the epidermal thickness and inflammatory response were significantly reduced in Imiquimod (IMQ)-induced psoriasis mice by applying with L-THE on mice skin. The expression of proliferation and inflammation associated genes such as keratin 17, IL-23 and CXCL1-3 was also downregulated by L-THE. Furthermore, L-THE inhibited the production of IL-23 in dendritic cells (DCs) after IMQ treatment, and decreased the levels of chemokines in keratinocytes treated with IL-17A by downregulating the expression of IL-17RA. RNA-seq and KEGG analysis revealed that L-THE significantly regulated the expression of IL-17A and NF-κB signaling pathway-associated genes. Metabolomics analysis displayed that L-THE promoted propanoate metabolism which has been reported to inhibit the activity of TH17 cells. Therefore, our results demonstrated that L-THE significantly decreases the levels of IL-23 and chemokines, and attenuates IMQ-induced psoriasis like skin inflammation by inhibiting the activation of NF‐κB and IL-17A signaling pathways, and promoting the propanoate metabolism. Our findings suggest that topical applied L-THE can be used as a topical drug candidate for the treatment of psoriasis or as an adjuvant treatment of ustekinumab or secukinumab to prevent the relapse of psoriasis.